2022
DOI: 10.1371/journal.pone.0276668
|View full text |Cite
|
Sign up to set email alerts
|

The relative age effect in top 100 elite female tennis players in 2007–2016

Abstract: The Relative Age Effect (RAE) has been the subject of many studies, but few have focused on professional athletes in individual sports. The aim of this study was to verify the existence of the RAE among elite senior female tennis players (top 100 players) in the WTA Rankings (n = 1000) in the years 2007–2016. The analysis was performed among top 100, resp. top 10 female tennis players, among players in 4 age subgroups and among left-handed (LH) and right-handed (RH) players. The existence of the RAE was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…We compared and analyzed the birth dates of athletes with various levels of achievement within the same age categories and investigated the impact of birth dates on athletic performance. The RAE was found to be present in all groups of Chinese junior female tennis players, and the observations were consistent with those found in some other female sports [50,51] and in tennis [11,[35][36][37][38]. Our study identified the presence of the RAE for the first time in Chinese junior female tennis, providing a foundation for further research on RAE mitigation programs and other studies in Chinese youth sports.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We compared and analyzed the birth dates of athletes with various levels of achievement within the same age categories and investigated the impact of birth dates on athletic performance. The RAE was found to be present in all groups of Chinese junior female tennis players, and the observations were consistent with those found in some other female sports [50,51] and in tennis [11,[35][36][37][38]. Our study identified the presence of the RAE for the first time in Chinese junior female tennis, providing a foundation for further research on RAE mitigation programs and other studies in Chinese youth sports.…”
Section: Discussionsupporting
confidence: 88%
“…The earliest research report on the RAE was in the field of education [ 3 ], while in the field of sports, Grondin et al [ 4 ] first observed the RAE in hockey, and Barnsley et al [ 2 ] discovered an RAE in sports during the same period. The RAE has been repeatedly discovered in sports over the past 10 years of research, including in basketball [ 5 , 6 ], soccer [ 1 , 7 , 8 ], volleyball [ 9 , 10 ], and tennis [ 11 ]. Moreover, reports on the impact of the RAE have been published with regard to sports [ 2 , 12 , 13 ], education systems [ 14 16 ], specific medical diagnoses [ 17 , 18 ], and cognitive tasks [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricola et al [ 44 ] found a clear predominance of athletes born in the first half of the year among athletes at the 2007–2011 World Junior Tennis Championships. This dominance extended from junior tennis players to high-level professional athletes, and the presence of the RAE was also still found in both the top 10 WTA ranked athletes [ 54 ] and the top ATP ranked athletes [ 42 ]. The above results suggest that younger players with tremendous potential are consequently less likely to be selected for elite teams [ 47 ] and more likely to withdraw [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the ranked players (N = 3.463) were classified based on their 2021 year-end ranking according to each age group from 10-to 17-years-old. After allocation, the subjects were divided into two groups, boys and girls, and each gender group was assigned to one of the four quartiles according to the month of birth: a) Quartile (Zháněl, Válek, Bozděch, & Agricola, 2022). The birth data of the general population was collected from the General Directorate of Civil Registration and Citizenship Affairs.…”
Section: Data Collectionmentioning
confidence: 99%